Investigation of Changes in Library Usage after the Introduction of Outsourcing in Japan - Mizunuma, Yuhiro; Tsuji, Keita (Qualitative and Quantitative Methods in Libraries, 2019)
In Japan, local governments have long managed public libraries; however, in 2003, organizations including private enterprises took over their management with the introduction of an outsourcing system, namely the “designated administrator system.” Now, whether local governments should apply this system to public libraries is under discussion, and many argue that it is inappropriate for public libraries. To provide basic data for such discussions, we investigated changes in library usage after the introduction of outsourcing. Specifically, we obtained statistics on library usage such as the gate count, number of loans, and number of reference transactions, and measured changes in these statistics before and after the introduction of outsourcing. The results show that the statistics tended to increase after the introduction of outsourcing. This may suggest that the introduction of outsourcing promotes users’ library usage.